Overcoming barriers to achieving a Net Zero agri-food sector: Challenges and solutions - Ryan G. McGuire; Lynda S. Perkins; Katie Lawther; Josh P. Thompson; Ilias Kyriazakis; Jørgen Eivind Olesen; Sharon Huws; Paul N. Williams; Taro Takahashi; Rachel Cassidy; Elizabeth Magowan; John Gilliland; et al. (Environmental Science & Policy, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Erratum to “Air pollution is linked to divergent cortical thickness patterns in brain regions vulnerable to Alzheimer’s disease” [Neurotoxicology 115 (2026) 103495] - Lauren E. Salminen; Xinhui Wang; Andrew J. Petkus; Christine Fennema-Notestine; Jeremy A. Elman; Donald J. Hagler; Joel D. Kaufman; Joshua Millstein; Meredith N. Braskie; Joshua Liu; Hyung Jin Cho; Deydeep Kothapalli; et al. (NeuroToxicology, 2026)

Air pollution is linked to divergent cortical thickness patterns in brain regions vulnerable to Alzheimer’s disease - Lauren E. Salminen; Xinhui Wang; Andrew J. Petkus; Christine Fennema-Notestine; Jeremy A. Elman; Donald J. Hagler; Joel D. Kaufman; Joshua Millstein; Meredith N. Braskie; Joshua Liu; Hyung Jin Cho; Deydeep Kothapalli; et al. (NeuroToxicology, 2026)

Developing a methodology to identify personalities in farmed red deer - B.R. Thompson; D.R. Stevens; I.J. Gordon; T.M.R. Maxwell; S. Zydenbos; K.G. Dodds; D. Triadis; P. Gregorini (Applied Animal Behaviour Science, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Oyster Size Distributions Vary Across Time and Space in the Tampa Bay Estuary, 250–2024 ce - Jaime A. Rogers; Thomas J. Pluckhahn; Kendal Jackson; Gregory S. Herbert; Stephen P. Geiger; Victor D. Thompson (Journal of Biogeography, 2026)
Aim Restoration benchmarks often assume an undisturbed historic range of variability, if they include historic information at all. However, recent research highlights the need for a more nuanced understanding of shifting baselines and how to best incorporate past variabilities in modern management. We investigate trends in oyster size through time (ca. 250–2024 ce ) and space (ca. 1000 km 2 ) in the Tampa Bay Estuary to understand when and where ecologically significant changes to oyster populations occurred. By implementing a multiscalar approach, this study contributes historical ecological data relevant to contemporary restoration and management efforts and provides insights into understanding long‐term socioecological dynamics in Florida's largest open‐water estuary. Location Tampa Bay Estuary, Florida, USA. Time Period ca. 250–2024 ce . Taxon Mollusca; Crassostrea virginica . Methods We measured sizes of over 15,000 oyster shells from archaeological sites and contemporary reefs across four estuarine sub‐basins over approximately 2000 years to assess how mean and maximum shell sizes responded to shifts in climate and human harvesting and settlement patterns. Results We demonstrate a non‐linear decline in oyster sizes through time, including a steep decline in oyster size prior to European colonization and commercial harvest. Changes in oyster size varied across sub‐regions, and there was no consistent response to climatic variability. A moderate rebound in oyster size during the 19th century is evident and coincides with several social factors that alleviated harvest pressures for a relatively short period. However, most of the largest contemporary oysters remain significantly smaller than those in the deeper past. Main Conclusions Archaeological datasets provide relevant historical ecological information for understanding modern era declines in molluscs. Our data reveal that no single baseline exists for oyster size in Tampa Bay. Instead, oyster populations responded in complex ways to climatic variability, ecological stressors and human interactions. Oyster size is a valuable functional trait linked to reproduction and reef resilience, and management targets that reference past demographic states should be framed as dynamic ranges and evaluated at sub‐regional scales.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Mulching promotes soil health and carbon sequestration in arid urban landscapes - Juan P. Frene; Pramod Acharya; Marisa Thompson; Amrit D. Adhikari; Rajan Ghimire (Urban Ecosystems, 2026)

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

Association between late-life air pollution exposure and medial temporal lobe atrophy in older women - Xinhui Wang; Lauren E. Salminen; Andrew J. Petkus; Ira Frahmand; Joshua Millstein; Daniel P. Beavers; Mark A. Espeland; Guray Erus; Meredith N. Braskie; Paul M. Thompson; Margaret Gatz; Helena C. Chui; et al. (NeuroToxicology, 2026)

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Longer WIC Participation Is Associated With Higher Diet Quality and Consumption of WIC-Eligible Foods Among Children 2-5 Years Old - Lauren E. Au; Hannah R. Thompson; Lorrene D. Ritchie; Brenda Sun; Thea P. Zimmerman; Shannon E. Whaley; Amanda Reat; Kavitha Sankavaram; Christine Borger (Journal of the Academy of Nutrition and Dietetics, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

The Greatest Extinction Event in 66 Million Years? Contextualising Anthropogenic Extinctions - Jack H. Hatfield; Bethany J. Allen; Tadhg Carroll; Christopher D. Dean; Shuyu Deng; Jonathan D. Gordon; Thomas Guillerme; James P. Hansford; Jennifer F. Hoyal Cuthill; Philip D. Mannion; Inês S. Martins; Alexander R. D. Payne; et al. (Global Change Biology, 2025)
Biological communities are changing rapidly in response to human activities, with the high rate of vertebrate species extinction leading many to propose that we are in the midst of a sixth mass extinction event. Five past mass extinction events have commonly been identified across the Phanerozoic, with the last occurring at the end of the Cretaceous, 66 million years ago (Ma). However, life on Earth has always changed and evolved, with most species ever to have existed now extinct. The question is, are human activities increasing the rate and magnitude of extinction to levels rarely seen in the history of life? Drawing on the literature on extinctions primarily over the last 66 million years (i.e., the Cenozoic), we ask: (1) what comparisons can meaningfully be drawn? and (2) when did the Earth last witness an extinction event on this scale? We conclude that, although challenging to address, the available evidence suggests that the ongoing extinction episode still falls a long way short of the devastation caused by the bolide impact 66 Ma, but that it has likely surpassed most other Cenozoic events in magnitude, with the possible exception of the Eocene–Oligocene transition (34 Ma), about which much uncertainty remains. Given the number of endangered and at‐risk species, the eventual magnitude of the current event will depend heavily on humanity's response and how we interact with the rest of the biosphere over the coming millennia.

Continental Patterns of Phenotypic Variation Along Replicated Urban Gradients: A Mega‐Analysis - M. J. Thompson; J. G. A. Martin; C. Biard; J. Bleu; C. J. Branston; P. Capilla‐Lasheras; N. J. Dingemanse; D. M. Dominoni; M. Eens; T. Eeva; K. L. Evans; C. Isaksson; et al. (Ecology Letters, 2025)
Individual variation among and within natural populations can have eco‐evolutionary implications by, for example, affecting species interactions or evolutionary potential. Urban systems present a unique opportunity to evaluate how environmental change shapes variation since urban phenotypic differentiation is widely documented on contemporary timescales. We introduce and test three hypotheses to determine how urbanisation affects phenotypic variation at different population levels. Combining 21 long‐term datasets in a mega‐analysis approach, we synthesise how urbanisation impacts variation in tarsus length and lay date among and within subpopulations of great and blue tits ( Parus major , Cyanistes caeruleus ) at a continental scale. Our synthesis reveals that urbanisation is associated with increased phenotypic variation within subpopulations by 11% on average, and by as much as 25% across the species and traits examined. We also find some evidence (for tarsus length in great tits) that urbanisation increases differentiation between subpopulations. We did not, however, find that urbanisation increases differences between subpopulations in their within‐subpopulation variation. Our synthesis provides novel insights into how urban contexts impact individual diversity at different spatial scales and we highlight future directions that could establish the genetic and environmental effects that underlie these continental patterns of urban phenotypic variation.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

A cross-sectional study of keratoconjunctivitis among dairy cattle farms subject to Mediterranean climatic conditions - L. H. Maartens; P. N. Thompson; J. D. Grewar; J. Picard; B. Gummow (Tropical Animal Health and Production, 2025)
The epidemiology of bovine keratoconjunctivitis (BK) is complex and involves several conjunctival microbiota as well as host and environmental factors. Data about BK in dairy cattle are scarce, and even scarcer for dairy cattle in Mediterranean climates. We determined the BK prevalence among dairy cattle in Southern Africa’s Mediterranean climatic zone by examining 1,675 dairy cattle across 28 herds. Conjunctival swabs were analysed using real-time PCR. Risk factor data were collected by questionnaire and evaluated by multivariable logistic regression. The BK prevalence was 19.4%, (95% CI: 15.0 – 24.8%). Mesomycoplasma bovoculi was demonstrated in 75.7% of the sampled eyes (95% CI: 62.8 – 85.2%) across all farms. Moraxella bovis (18.3%, 95% CI: 11.9 – 27.0%) and Moraxella bovoculi (8.6%, 95% CI: 4.6 – 15.6%) were detected on 89% and 64% of the farms, respectively. Mycoplasmopsis bovis was rarely encountered. Moraxella bovoculi was significantly associated with BK (OR: 2.7, 95% CI: 1.3 – 5.6, Wald P : 0.01). Prevalence varied significantly by age and breed. Shade availability (OR: 2.5, 95% CI: 1.4 – 4.4, Wald P < 0.01), sanitation frequency, (OR: 0.4, 95% CI: 0.2 – 1.0, Wald P : 0.05), fly burden (OR: 2.1, 95% CI: 1.3 – 3.6, Wald P < 0.01) and introduced cattle (OR: 2.0, 95% CI: 1.1 – 3.5, Wald P : 0.02) were significantly associated with the prevalence of BK. Closed herds with proper biosecurity, fly control via sound management practices, and access to shade are recommended for preventing BK in dairy herds farmed in a Mediterranean climate.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

The application of digital tools for knowledge sharing in agriculture: A longitudinal case study from four Australian grower groups - A. Ollerenshaw; H. Thompson; H. Luke; P. Cooke; F. Best; N. Scholz; D. Fear; N. Craig; J. Telfer; A. Wright; S. Kruger (Computers and Electronics in Agriculture, 2025)

Reply to “timing errors in global sea level observations” (Pan et al., 2025) - Philip R. Thompson; Ayesha S. Genz; Matthew J. Widlansky; Gary T. Mitchum; Elizabeth Bradshaw; Adam T. Devlin; Begoña P. Gómez; Ivan D. Haigh; Marta Marcos; Andrew Matthews; Mark A. Merrifield (Ocean Dynamics, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Nitrogen and Spacing Requirements for Advanced Chipping Selections ND7799c-1 and ND7519-1 - Jed D. Grow; Asunta L. Thompson; Gary A. Secor; Andrew P. Robinson (American Journal of Potato Research, 2024)
Adoption of new cultivars is challenging for commercial growers. To understand the best nitrogen fertilization rate (90, 134, 179, and 224 kg N ha -1 ) and within-row spacing (15, 23 and 31 cm) for two potential potato cultivar releases from North Dakota State University, a study was carried out in 2019 and 2020 in North Dakota. The advanced chipping selections ND7799c-1 and ND7519-1 were compared to a chip industry standard, Dakota Pearl. In 2019, ND7799c-1 grown at 23 cm within-row spacing had similar marketable yield to Dakota Pearl. In 2020, ND7519-1 at all within-row spacings, and ND7799c-1 at 15 and 23 cm within-row spacing, yielded similarly to Dakota Pearl. Nitrogen rate did not affect yield or chipping quality in 2019 or 2020. The advanced selections had lower sucrose and glucose levels one month after harvest compared to Dakota Pearl in 2020. ND7799c-1 stored for 8 months, and ND7519-1 for 6 months, before chip quality declined. This research demonstrates the potential for ND7799c-1 and ND7519-1 to be successful chip processing cultivars for the Northern Plains.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Grazing herbivores reduce herbaceous biomass and fire activity across African savannas - A. Tyler Karp; Sally E. Koerner; Gareth P. Hempson; Joel O. Abraham; T. Michael Anderson; William J. Bond; Deron E. Burkepile; Elizabeth N. Fillion; Jacob R. Goheen; Jennifer A. Guyton; Tyler R. Kartzinel; Duncan M. Kimuyu; et al. (Ecology Letters, 2024)
Fire and herbivory interact to alter ecosystems and carbon cycling. In savannas, herbivores can reduce fire activity by removing grass biomass, but the size of these effects and what regulates them remain uncertain. To examine grazing effects on fuels and fire regimes across African savannas, we combined data from herbivore exclosure experiments with remotely sensed data on fire activity and herbivore density. We show that, broadly across African savannas, grazing herbivores substantially reduce both herbaceous biomass and fire activity. The size of these effects was strongly associated with grazing herbivore densities, and surprisingly, was mostly consistent across different environments. A one‐zebra increase in herbivore biomass density (~100 kg/km 2 of metabolic biomass) resulted in a ~53 kg/ha reduction in standing herbaceous biomass and a ~0.43 percentage point reduction in burned area. Our results indicate that fire models can be improved by incorporating grazing effects on grass biomass.

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Deep learning of estuary salinity dynamics is physically accurate at a fraction of hydrodynamic model computational cost - Galen Gorski; Salme Cook; Amelia Snyder; Alison P. Appling; Theodore Thompson; Jared D. Smith; John C. Warner; Simon N. Topp (Limnology and Oceanography, 2024)
Salinity dynamics in the Delaware Bay estuary are a critical water quality concern as elevated salinity can damage infrastructure and threaten drinking water supplies. Current state‐of‐the‐art modeling approaches use hydrodynamic models, which can produce accurate results but are limited by significant computational costs. We developed a machine learning (ML) model to predict the 250 mg L −1 Cl − isochlor, also known as the “salt front,” using daily river discharge, meteorological drivers, and tidal water level data. We use the ML model to predict the location of the salt front, measured in river miles (RM) along the Delaware River, during the period 2001–2020, and we compare predictions of the ML model to the hydrodynamic Coupled Ocean–Atmosphere‐Wave‐Sediment Transport (COAWST) model. The ML model predicts the location of the salt front with greater accuracy (root mean squared error [RMSE] = 2.52 RM) than the COAWST model does (RMSE = 5.36); however, the ML model struggles to predict extreme events. Furthermore, we use functional performance and expected gradients, tools from information theory and explainable artificial intelligence, to show that the ML model learns physically realistic relationships between the salt front location and drivers (particularly discharge and tidal water level). These results demonstrate how an ML modeling approach can provide predictive and functional accuracy at a significantly reduced computational cost compared to process‐based models. In addition, these results provide support for using ML models in operational forecasting, scenario testing, management decisions, hindcasting, and resulting opportunities to understand past behavior and develop hypotheses.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Assessment of oceanographic conditions during the North Atlantic EXport processes in the ocean from RemoTe sensing (EXPORTS) field campaign - Leah Johnson; David A. Siegel; Andrew F. Thompson; Erik Fields; Zachary K. Erickson; Ivona Cetinic; Craig M. Lee; Eric A. D'Asaro; Norman B. Nelson; Melissa M. Omand; Michaela Sten; Shawnee Traylor; et al. (Progress in Oceanography, 2024)

A paleoecological investigation of recent cyanobacterial blooms and their drivers in two contrasting lakes - Caitlin Wheeler; John K. Pearman; Jamie D. Howarth; Marcus J. Vandergoes; Katherine Holt; Steven A. Trewick; Xun Li; Lucy Thompson; Georgia Thomson-Laing; Mailys Picard; Chris Moy; Nicholas P. Mckay; et al. (Harmful Algae, 2024)

A critical re‐analysis of constraints on the timing and rate of Laurentide Ice Sheet recession in the northeastern United States - Christopher T. Halsted; Paul R. Bierman; Jeremy D. Shakun; P. Thompson Davis; Lee B. Corbett; Jason S. Drebber; John C. Ridge (Journal of Quaternary Science, 2024)
We review geochronological data relating to the timing and rate of Laurentide Ice Sheet recession in the northeastern United States and model ice margin movements in a Bayesian framework using compilations of previously published organic 14 C ( n = 133) and in situ cosmogenic 10 Be ( n = 95) ages. We compare the resulting method‐specific chronologies with glacial varve records that serve as independent constraints on the pace of ice recession to: (1) construct a synthesis of deglacial chronology throughout the region; and (2) assess the accuracy of each chronometer for constraining the timing of deglaciation. Near the Last Glacial Maximum terminal moraine zone, 10 Be and organic 14 C ages disagree by thousands of years and limit determination of the initial recession to a date range of 24–20 ka. We infer that 10 Be inherited from pre‐glacial exposure adds 2–6 kyr to many exposure ages near the terminal moraines, whereas macrofossil 14 C ages are typically 4–8 kyr too young due to a substantial lag between ice recession and sufficient organic material accumulation for dating in some basins. Age discrepancies between these chronometers decrease with distance from the terminal moraine, due to less 10 Be inherited from prior exposure and a reduced lag between ice recession and organic material deposition. 14 C and 10 Be ages generally agree at locations more than 200 km distal from the terminal moraines and suggest a mostly continuous history of ice recession throughout the region from 18 to 13 ka with a variable pace best documented by varves.

Offsets in tide-gauge reference levels detected by satellite altimetry: ten case studies - R. D. Ray; M. J. Widlansky; A. S. Genz; P. R. Thompson (Journal of Geodesy, 2023)
Comparing measurements of absolute sea level by satellite altimetry and relative sea level by a tide gauge can reveal errors in either measurement system. Combining the measurements can determine vertical land motion (VLM) at the tide gauge. We here discuss ten case studies in which a tide gauge has likely experienced a small ( $$\le 10$$ ≤ 10 cm), discontinuous offset in the vertical, suggesting inadvertent loss of reference-level stability. Proper interpretation of offsets is helped if independent VLM measurements from nearby geodetic stations are available. In two cases, earthquake-induced VLM cannot be ruled out, although it appears unlikely. Offsets as small as 1–2 cm can be detected when both altimeter and tide gauge successfully observe the same ocean signal. This is most likely to occur for tide gauges located on small, open-ocean islands. Tide gauges near large land masses are typically more challenging owing to inadequacies of satellite altimetry near land and to differences between coastal and open-ocean sea levels. The case studies highlight the utility of satellite altimetry for tide-gauge quality control.

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Insight into characteristics and pathogenicity of five rapidly growing non-tuberculous Mycobacterium species isolated from the Siamese fighting fish, Betta splendens - Nguyen Dinh-Hung; Ha Thanh Dong; Saengchan Senapin; Khaettareeya Pimsannil; Kim D. Thompson; Andrew P. Shinn; Chayanit Soontara; Wanna Sirimanapong; Satid Chatchaiphan; Channarong Rodkhum (Aquaculture, 2023)

Thermal hydraulic and mechanical modelling of the full-scale in situ test (FISST) - V. Tsitsopoulos; D. Holton; P. Appleyard; S. Thompson; S. Baxter; M. Niskanen (Engineering Geology, 2023)

Compositional shifts of alpine plant communities across the high Andes - F. Cuesta; J. Carilla; L. D. LLambí; P. Muriel; M. V. Lencinas; R. I. Meneses; K. J. Feeley; H. Pauli; N. Aguirre; S. Beck; A. Bernardi; S. Cuello; et al. (Global Ecology and Biogeography, 2023)
Aim Climate change is transforming mountain summit plant communities worldwide, but we know little about such changes in the High Andes. Understanding large‐scale patterns of vegetation changes across the Andes, and the factors driving these changes, is fundamental to predicting the effects of global warming. We assessed trends in vegetation cover, species richness (SR) and community‐level thermal niches (CTN) and tested whether they are explained by summits' climatic conditions and soil temperature trends. Location High Andes. Time period Between 2011/2012 and 2017/2019. Major taxa studied Vascular plants. Methods Using permanent vegetation plots placed on 45 mountain summits and soil temperature loggers situated along a ~6800 km N‐S gradient, we measured species and their relative percentage cover and estimated CTN in two surveys (intervals between 5 and 8 years). We then estimated the annual rate of changes for the three variables and used generalized linear models to assess their relationship with annual precipitation, the minimum air temperatures of each summit and rates of change in the locally recorded soil temperatures. Results Over time, there was an average loss of vegetation cover (mean = −0.26%/yr), and a gain in SR across summits (mean = 0.38 species m 2 /yr), but most summits had significant increases in SR and vegetation cover. Changes in SR were positively related to minimum air temperature and soil temperature rate of change. Most plant communities experienced shifts in their composition by including greater abundances of species with broader thermal niches and higher optima. However, the measured changes in soil temperature did not explain the observed changes in CTN. Main conclusions High Andean vegetation is changing in cover and SR and is shifting towards species with wider thermal niche breadths. The weak relationship with soil temperature trends could have resulted from the short study period that only marginally captures changes in vegetation through time.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

From the Lebombo Monocline to the Mozambique Deep Basin, using combined wide-angle and reflection seismic data - M. Moulin; A. Leprêtre; F. Verrier; P. Schnürle; M. Evain; P. de Clarens; J. Thompson; N. Dias; A. Afilhado; A. Loureiro; D. Aslanian (Tectonophysics, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Novel DNA‐based in situ hybridization method to detect Desmozoon lepeophtherii in Atlantic salmon tissues - Ana Herrero; Oswaldo Palenzuela; Hamish Rodger; Chris Matthews; Mar Marcos‐López; James E. Bron; Mark P. Dagleish; Kim D. Thompson (Journal of Fish Diseases, 2022)
The microsporidian Desmozoon lepeophtherii Freeman and Sommerville, 2009 is considered significant in the pathogenesis of gill disease in Atlantic salmon ( Salmo salar Linnaeus, 1758). Due to the difficulty in detecting D. lepeophtherii in tissue sections, infections are normally diagnosed by molecular methods, routine haematoxylin and eosin (H&E) stained gill tissue sections and the use of other histochemical stains and labels to confirm the presence of spores. An in situ hybridization (ISH) protocol specific for D. lepeophtherii was developed using DIG‐labelled oligonucleotide probes. Diseased Atlantic salmon gills were analysed by ISH, calcofluor white (CW) and H&E. All methods showed high levels of specificity (100%) in their ability to detect D. lepeophtherii , but the sensitivity was higher with ISH (92%), compared with CW (64%) and the presence of microvesicles on H&E stained sections (52%). High levels of D. lepeophtherii spores were significantly associated ( p D. lepeophtherii ‐associated pathology in the gills, with Ct values below 19 and over 100 microsporidia/10 mm 2 of gill tissue (from the ISH counts) seemingly necessary for the development of microvesicles. The ISH method has the advantage over other histological techniques in that it allows all life stages of the microsporidian to be detected in infected salmon gill tissue sections.

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

ENIGMA + COINSTAC: Improving Findability, Accessibility, Interoperability, and Re-usability - Jessica A. Turner; Vince D. Calhoun; Paul M. Thompson; Neda Jahanshad; Christopher R. K. Ching; Sophia I. Thomopoulos; Eric Verner; Gregory P. Strauss; Anthony O. Ahmed; Matthew D. Turner; Sunitha Basodi; Judith M. Ford; et al. (Neuroinformatics, 2022)
The FAIR principles, as applied to clinical and neuroimaging data, reflect the goal of making research products F indable, A ccessible, I nteroperable, and R eusable. The use of the Collaborative Informatics and Neuroimaging Suite Toolkit for Anonymized Computation (COINSTAC) platform in the Enhancing Neuroimaging Genetics through Meta-Analysis (ENIGMA) consortium combines the technological approach of decentralized analyses with the sociological approach of sharing data. In addition, ENIGMA + COINSTAC provides a platform to facilitate the use of machine-actionable data objects. We first present how ENIGMA and COINSTAC support the FAIR principles, and then showcase their integration with a decentralized meta-analysis of sex differences in negative symptom severity in schizophrenia, and finally present ongoing activities and plans to advance FAIR principles in ENIGMA + COINSTAC. ENIGMA and COINSTAC currently represent efforts toward improved Access, Interoperability, and Reusability. We highlight additional improvements needed in these areas, as well as future connections to other resources for expanded Findability.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Pancreatic cancer pathology viewed in the light of evolution - Michaël Noë; Seung-Mo Hong; Laura D. Wood; Elizabeth D. Thompson; Nicholas J. Roberts; Michael G. Goggins; Alison P. Klein; James R. Eshleman; Scott E. Kern; Ralph H. Hruban (Cancer and Metastasis Reviews, 2021)
One way to understand ductal adenocarcinoma of the pancreas (pancreatic cancer) is to view it as unimaginably large numbers of evolving living organisms interacting with their environment. This “evolutionary view” creates both expected and surprising perspectives in all stages of neoplastic progression. Advances in the field will require greater attention to this critical evolutionary prospective.

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Genome sequence of Vibrio fluvialis 362.3 isolated from coral Mussismilia braziliensis reveals genes related to marine environment adaptation - Livia M. R. Vidal; Aline R. P. Gonçalves; Tainá M. Venas; Gizele D. Garcia; Diogo A. Tschoeke; Fabiano L. Thompson; Cristiane C. Thompson (Archives of Microbiology, 2021)

Challenging the Need for Deep Seabed Mining From the Perspective of Metal Demand, Biodiversity, Ecosystems Services, and Benefit Sharing - K. A. Miller; K. Brigden; D. Santillo; D. Currie; P. Johnston; K. F. Thompson (Frontiers in Marine Science, 2021)
The extraction of minerals from the seabed of the deep oceans is of increasing interest to investors, mining companies and some coastal states. To date, no commercial-scale deep seabed mining has taken place but there is considerable pressure for minerals mining to become an economic reality, including to supply the projected demand for metals to support a global transition to renewable energy. At the same time, the full environmental impacts of deep seabed mining are difficult to predict but are expected to be highly damaging, both within, and perhaps well beyond, the areas mined. Here, we reflect on the considerable uncertainties that exist in relation to deep seabed mining. In particular, we provide a perspective on: (1) arguments that deep seabed mining is needed to supply minerals for the green energy revolution, using the electric vehicle battery industry as an illustration; (2) risks to biodiversity, ecosystem function and related ecosystem services; and (3) the lack of equitable benefit sharing to the global community now and for future generations. We explore the justification for a global moratorium on deep seabed mining to ensure protection of marine ecosystems, the need to focus on baseline research, and how improved governance of targeted marine regions could be key to the preservation and conservation of the ocean biome.

Pathogen infection influences a distinct microbial community composition in sorghum RILs - K. Masenya; G. D. Thompson; M. Tekere; T. P. Makhalanyane; R. E. Pierneef; D. J. G. Rees (Plant and Soil, 2021)
Aims The rhizosphere microbiome substantially affects plant health, yet comparatively little is known regarding the foliar community dynamics. Here, we examine the relationship between the microbiota and their response to natural infection by pathogens. Methods We established an experimental system using a set of sorghum recombinant inbred lines (RILS). These RILS included four models denoted as resistant, moderately resistant, susceptible and highly susceptible. A combination of 16S rRNA and ITS gene amplicon approaches was used to assess bacteria and fungi, respectively, in foliar samples. Results We show that the foliar microbiome differs substantially in asymptomatic and symptomatic RILs subsequent to natural infection by pathogens. A significant association was found between plant health and microbial community structure. Our analyses revealed several distinct fungal and bacterial pathogens. These pathogens included Gibberella and Pantoea genera, which were associated with the highly susceptible group. In addition to these pathogens, we also found signatures for Ascochyta , a known plant pathogenic genus. Members of the bacterial genus Methylorubrum and the fungal genus Hannaella, both known to exhibit plant growth-promoting (PGP) traits, were associated with the resistant and moderately resistant groups. These data also reveal numerous highly diverse fungal and bacterial taxa in RILs that did not show symptoms. We also found taxonomic differences between the microbiota hosted by the symptomatic and asymptomatic RILs. Conclusions Together, these data suggest that pathogen infection may result in distinct microbiota. These results suggest that highly diverse microbiome may promote the plants ability to resist the effects of pathogens potentially contributing to plant health.

Lipophilic Salts and Lipid-Based Formulations: Enhancing the Oral Delivery of Octreotide - Peng Li; Leigh Ford; Shadabul Haque; Mitchell P. McInerney; Hywel D. Williams; Peter J. Scammells; Philip E. Thompson; Vincent Jannin; Christopher J. H. Porter; Hassan Benameur; Colin W. Pouton (Pharmaceutical Research, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Cephalopods habitat and trophic ecology: historical data using snares penguin as biological sampler - H. R. Guímaro; D. R. Thompson; V. H. Paiva; F. R. Ceia; D. M. Cunningham; P. J. Moors; J. C. Xavier (Polar Biology, 2021)

Vibrio tetraodonis sp. nov.: genomic insights on the secondary metabolites repertoire - Gustavo P. R. Azevedo; Hannah K. Mattsson; Grasiele R. Lopes; Livia Vidal; Mariana Campeão; Luciane A. Chimetto Tonon; Gizele D. Garcia; Diogo A. Tschoeke; Bruno S. Silva; Koko Otsuki; Bruno Gomez-Gil; Jean Swings; et al. (Archives of Microbiology, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The Toxicology Investigators Consortium Case Registry—the 2019 Annual Report - Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Kim Aldy; Diane P. Calello; Sharan L. Campleman; Shao Li; Gillian A Beauchamp; Timothy Wiegand; Paul M. Wax; Jeffery Brent; P. A. Akpunonu; et al. (Journal of Medical Toxicology, 2020)

Rapid screening of marine bacterial symbionts using MALDI-TOF MS - Livia M. R. Vidal; Tainá M. Venas; Aline R. P. Gonçalves; Hannah K. Mattsson; Raphael V. P. Silva; Maria S. Nóbrega; Gustavo P. R. Azevedo; Gizele D. Garcia; Diogo A. Tschoeke; Verônica V. Vieira; Fabiano L. Thompson; Cristiane C. Thompson (Archives of Microbiology, 2020)

Weather underground: Subsurface hydrologic processes mediate tree vulnerability to extreme climatic drought - Blair C. McLaughlin; Rachel Blakey; Andrew P. Weitz; Xue Feng; Brittni J. Brown; David D. Ackerly; Todd E. Dawson; Sally E. Thompson (Global Change Biology, 2020)
Drought extent and severity have increased and are predicted to continue to increase in many parts of the world. Understanding tree vulnerability to drought at both individual and species levels is key to ongoing forest management and preparation for future transitions in community composition. The influence of subsurface hydrologic processes is particularly important in water‐limited ecosystems, and is an under‐studied aspect of tree drought vulnerability. With California's 2013–2016 extraordinary drought as a natural experiment, we studied four co‐occurring woodland tree species, blue oak ( Quercus douglasii ), valley oak ( Quercus lobata ), gray pine ( Pinus sabiniana ), and California juniper ( Juniperus californica ), examining drought vulnerability as a function of climate, lithology and hydrology using regional aerial dieback surveys and site‐scale field surveys. We found that in addition to climatic drought severity (i.e., rainfall), subsurface processes explained variation in drought vulnerability within and across species at both scales. Regionally for blue oak, severity of dieback was related to the bedrock lithology, with higher mortality on igneous and metamorphic substrates, and to regional reductions in groundwater. At the site scale, access to deep subsurface water, evidenced by stem water stable isotope composition, was related to canopy condition across all species. Along hillslope gradients, channel locations supported similar environments in terms of water stress across a wide climatic gradient, indicating that subsurface hydrology mediates species’ experience of drought, and that areas associated with persistent access to subsurface hydrologic resources may provide important refugia at species’ xeric range edges. Despite this persistent overall influence of the subsurface environment, individual species showed markedly different response patterns. We argue that hydrologic niche segregation can be a useful lens through which to interpret these differences in vulnerability to climatic drought and climate change.

Rapid recovery of ecosystem function following extreme drought in a South African savanna grassland - Kevin R. Wilcox; Sally E. Koerner; David L. Hoover; Andrea K. Borkenhagen; Deron E. Burkepile; Scott L. Collins; Ava M. Hoffman; Kevin P. Kirkman; Alan K. Knapp; Tercia Strydom; Dave I. Thompson; Melinda D. Smith (Ecology, 2020)
Climatic extremes, such as severe drought, are expected to increase in frequency and magnitude with climate change. Thus, identifying mechanisms of resilience is critical to predicting the vulnerability of ecosystems. An exceptional drought (

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Risk Management and Analytics in Wildfire Response - Matthew P. Thompson; Yu Wei; David E. Calkin; Christopher D. O’Connor; Christopher J. Dunn; Nathaniel M. Anderson; John S. Hogland (Current Forestry Reports, 2019)
Purpose of Review The objectives of this paper are to briefly review basic risk management and analytics concepts, describe their nexus in relation to wildfire response, demonstrate real-world application of analytics to support response decisions and organizational learning, and outline an analytics strategy for the future. Recent Findings Analytics can improve decision-making and organizational performance across a variety of areas from sports to business to real-time emergency response. A lack of robust descriptive analytics on wildfire incident response effectiveness is a bottleneck for developing operationally relevant and empirically credible predictive and prescriptive analytics to inform and guide strategic response decisions. Capitalizing on technology such as automated resource tracking and machine learning algorithms can help bridge gaps between monitoring, learning, and data-driven decision-making. Summary By investing in better collection, documentation, archiving, and analysis of operational data on response effectiveness, fire management organizations can promote systematic learning and provide a better evidence base to support response decisions. We describe an analytics management framework that can provide structure to help deploy analytics within organizations, and provide real-world examples of advanced fire analytics applied in the USA. To fully capitalize on the potential of analytics, organizations may need to catalyze cultural shifts that cultivate stronger appreciation for data-driven decision processes, and develop informed skeptics that effectively balance both judgment and analysis in decision-making.

Reconciling the contribution of environmental and stochastic structuring of tropical forest diversity through the lens of imaging spectroscopy - Boris Bongalov; David F. R. P. Burslem; Tommaso Jucker; Samuel E. D. Thompson; James Rosindell; Tom Swinfield; Reuben Nilus; Daniel Clewley; Oliver L. Phillips; David A. Coomes (Ecology Letters, 2019)
Both niche and stochastic dispersal processes structure the extraordinary diversity of tropical plants, but determining their relative contributions has proven challenging. We address this question using airborne imaging spectroscopy to estimate canopy β‐diversity for an extensive region of a Bornean rainforest and challenge these data with models incorporating niches and dispersal. We show that remotely sensed and field‐derived estimates of pairwise dissimilarity in community composition are closely matched, proving the applicability of imaging spectroscopy to provide β‐diversity data for entire landscapes of over 1000 ha containing contrasting forest types. Our model reproduces the empirical data well and shows that the ecological processes maintaining tropical forest diversity are scale dependent. Patterns of β‐diversity are shaped by stochastic dispersal processes acting locally whilst environmental processes act over a wider range of scales.

Identification of a novel species of Eimeria Schneider, 1875 from the woylie, Bettongia penicillata Gray (Diprotodontia: Potoroidae) and the genetic characterisation of three Eimeria spp. from other potoroid marsupials - Amy S. Northover; Sarah Keatley; Aileen D. Elliot; Russell P. Hobbs; Rongchang Yang; Alan J. Lymbery; Stephanie S. Godfrey; Adrian F. Wayne; R. C. Andrew Thompson (Systematic Parasitology, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Exploration of Shared Genetic Architecture Between Subcortical Brain Volumes and Anorexia Nervosa - E. Walton; D. Hibar; Z. Yilmaz; N. Jahanshad; J. Cheung; V.-L. Batury; J. Seitz; C. M. Bulik; P. M. Thompson; Stefan Ehrlich (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Oocyte quality and viability in Nguni and Hereford cows exposed to different levels of dietary protein - R. Hamman; P. N. Thompson; M. P. Smuts; T. Tshuma; D. E. Holm (Tropical Animal Health and Production, 2019)

Gut microbiome and brain functional connectivity in infants-a preliminary study focusing on the amygdala - Wei Gao; Andrew P. Salzwedel; Alexander L. Carlson; Kai Xia; M. Andrea Azcarate-Peril; Martin A. Styner; Amanda L. Thompson; Xiujuan Geng; Barbara D. Goldman; John H. Gilmore; Rebecca C. Knickmeyer (Psychopharmacology, 2019)

Relationships Between Estimated Hourly Energy Balance and Body Composition in Professional Cheerleaders - Moriah P. Bellissimo; Ashley D. Licata; Anita Nucci; Walter Thompson; Dan Benardot (Journal of Science in Sport and Exercise, 2019)

Efficacy of a polyvalent injectable vaccine against Flavobacterium psychrophilum administered to rainbow trout ( Oncorhynchus mykiss L.) - Rowena Hoare; Sung‐Ju Jung; Thao P. H. Ngo; Kerry L. Bartie; Kim D. Thompson; Alexandra Adams (Journal of Fish Diseases, 2019)
Flavobacterium psychrophilum is one of the most important pathogens affecting cultured rainbow trout ( Oncorhynchus mykiss ). Recent information from UK salmonid farms showed country‐wide distribution of genetically and serologically divergent clones, which has hampered the development of a vaccine for rainbow trout fry syndrome. The current study assessed the efficacy of an injectable polyvalent vaccine containing formalin‐inactivated F. psychrophilum in rainbow trout. The vaccine was formulated with an oil adjuvant (Montanide ISA 760VG) or formalin‐killed cells alone. Duplicate groups of trout (60 ± 13 g) were given phosphate‐buffered saline or vaccine formulated with Montanide by intra‐peritoneal (i.p.) injection and challenged by intra‐muscular (i.m.) injection with a homologous and a heterologous isolate of F. psychrophilum at 525 degree days post‐vaccination (dd pv). Significant protection was achieved in vaccinated fish ( p = 0.0001, RPS 76% homologous, 88% heterologous). Efficacy of the adjuvanted vaccine was also demonstrated by heterologous challenge at 1155 dd pv resulting in 100% protection, whereas survival in the un‐adjuvanted group was not significantly different from control fish. Levels of specific antibody at 1155 dd pv, as measured by ELISA, were significantly higher in the fish vaccinated with adjuvant when compared with unvaccinated fish.

The ecohydrological context of drought and classification of plant responses - Xue Feng; David D. Ackerly; Todd E. Dawson; Stefano Manzoni; Rob P. Skelton; Giulia Vico; Sally E. Thompson (Ecology Letters, 2018)
Many recent studies on drought‐induced vegetation mortality have explored how plant functional traits, and classifications of such traits along axes of, for example, isohydry–anisohydry, might contribute to predicting drought survival and recovery. As these studies proliferate, the consistency and predictive value of such classifications need to be carefully examined. Here, we outline the basis for a systematic classification of plant drought responses that accounts for both environmental conditions and functional traits. We use non‐dimensional analysis to integrate plant traits and metrics of environmental variation into groups that can be associated with alternative drought stress pathways (hydraulic failure and carbon limitation), and demonstrate that these groupings predict physiological drought outcomes using both synthetic and measured data. In doing so, we aim to untangle some confounding effects of environment and trait variations that undermine current classification schemes, advocate for more careful treatment of the environmental context within which plants experience and respond to drought, and outline a pathway towards a general classification of drought vulnerability.

Longitudinal Preterm Cerebellar Volume: Perinatal and Neurodevelopmental Outcome Associations - Lillian G. Matthews; T. E. Inder; L. Pascoe; K. Kapur; K. J. Lee; B. B. Monson; L. W. Doyle; D. K. Thompson; P. J. Anderson (The Cerebellum, 2018)

Eastern rockhopper penguins Eudyptes filholi as biological samplers of juvenile and sub-adult cephalopods around Campbell Island, New Zealand - J. C. Xavier; Y. Cherel; F. R. Ceia; J. P. Queirós; B. Guimarães; R. Rosa; D. M. Cunningham; P. J. Moors; D. R. Thompson (Polar Biology, 2018)

Different types of drifts in two seasonal forecast systems and their dependence on ENSO - L Hermanson; H.-L. Ren; M. Vellinga; N. D. Dunstone; P. Hyder; S. Ineson; A. A. Scaife; D. M. Smith; V. Thompson; B. Tian; K. D. Williams (Climate Dynamics, 2018)

Marine Biotechnology in Brazil: Recent Developments and Its Potential for Innovation - Fabiano Thompson; Ricardo Krüger; Cristiane C. Thompson; Roberto G. S. Berlinck; Ricardo Coutinho; Melissa F. Landell; Mauro Pavão; Paulo A. S. Mourão; Ana Salles; Naiane Negri; Fabyano A. C. Lopes; Vitor Freire; et al. (Frontiers in Marine Science, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Blue-Green Water Nexus in Aquaculture for Resilience to Climate Change - Nesar Ahmed; James D. Ward; Shirley Thompson; Christopher P. Saint; James S. Diana (Reviews in Fisheries Science & Aquaculture, 2018)

Non-communicable chronic diseases and timely breast cancer screening among women of the Eastern Caribbean Health Outcomes Research Network (ECHORN) Cohort Study - K. H. Wang; T. A. Thompson; D. Galusha; H. Friedman; C. M. Nazario; M. Nunez; R. G. Maharaj; O. P. Adams; M. Nunez-Smith (Cancer Causes & Control, 2018)

Antimicrobial susceptibility of Flavobacterium psychrophilum isolates from the United Kingdom - T P H Ngo; P Smith; K L Bartie; K D Thompson; D W Verner‐Jeffreys; R Hoare; A Adams (Journal of Fish Diseases, 2018)
Routine application of antimicrobials is the current treatment of choice for rainbow trout fry syndrome ( RTFS ) or bacterial coldwater disease ( BCWD ) caused by Flavobacterium psychrophilum . In this study, the antimicrobial susceptibilities of 133 F. psychrophilum isolates, 118 of which were from the UK , were evaluated by broth microdilution and disc diffusion methods following VET 04‐A2 and VET 03‐A guidelines of Clinical and Laboratory Standards Institute ( CLSI ), respectively. Isolates were categorized as wild type (fully susceptible, WT ) or non‐wild type ( NWT ) using normalized resistance interpretation ( NRI )‐determined cut‐off values ( CO WT ). Broth microdilution testing showed that only 12% of UK isolates were WT to oxolinic acid ( MIC CO WT ≤ 0.25 mg/L) and 42% were WT for oxytetracycline ( MIC CO WT ≤ 0.25 mg/L). In contrast, all the isolates tested were WT ( MIC CO WT ≤ 2 mg/L) for florfenicol, the main antimicrobial for RTFS control in the UK . Disc diffusion‐based CO WT values were ≥51 mm for 10 μg amoxicillin, ≥44 mm for 30 μg florfenicol, ≥30 mm for 2 μg oxolinic acid and ≥51 mm for 30 μg oxytetracycline. There was a high categorical agreement between the classifications of the isolates by two testing methods for florfenicol (100%), oxytetracycline (93%) and oxolinic acid (99%).

Vulnerability of forests of the Midwest and Northeast United States to climate change - Chris Swanston; Leslie A. Brandt; Maria K. Janowiak; Stephen D. Handler; Patricia Butler-Leopold; Louis Iverson; Frank R. Thompson III; Todd A. Ontl; P. Danielle Shannon (Climatic Change, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Arbuscular mycorrhizas are present on Spitsbergen - K. K. Newsham; P. B. Eidesen; M. L. Davey; J. Axelsen; E. Courtecuisse; C. Flintrop; A. G. Johansson; M. Kiepert; S.E. Larsen; K. E. Lorberau; M. Maurset; J. McQuilkin; et al. (Mycorrhiza, 2017)

Facing a wicked problem with optimism: issues and priorities for coral conservation in Hong Kong - N. N. Duprey; S. E. McIlroy; T. P. T. Ng; P. D. Thompson; T. Kim; J. C. Y. Wong; C. W. M. Wong; S. M. Husa; S. M. H. Li; G. A. Williams; D. M. Baker (Biodiversity and Conservation, 2017)

Rapid divergence of animal personality and syndrome structure across an arid-aquatic habitat matrix - Nicholas P. Moran; Krystina D. Mossop; Ross M. Thompson; David G. Chapple; Bob B. M. Wong (Oecologia, 2017)

Hydrologic refugia, plants, and climate change - Blair C. McLaughlin; David D. Ackerly; P. Zion Klos; Jennifer Natali; Todd E. Dawson; Sally E. Thompson (Global Change Biology, 2017)
Climate, physical landscapes, and biota interact to generate heterogeneous hydrologic conditions in space and over time, which are reflected in spatial patterns of species distributions. As these species distributions respond to rapid climate change, microrefugia may support local species persistence in the face of deteriorating climatic suitability. Recent focus on temperature as a determinant of microrefugia insufficiently accounts for the importance of hydrologic processes and changing water availability with changing climate. Where water scarcity is a major limitation now or under future climates, hydrologic microrefugia are likely to prove essential for species persistence, particularly for sessile species and plants. Zones of high relative water availability – mesic microenvironments – are generated by a wide array of hydrologic processes, and may be loosely coupled to climatic processes and therefore buffered from climate change. Here, we review the mechanisms that generate mesic microenvironments and their likely robustness in the face of climate change. We argue that mesic microenvironments will act as species‐specific refugia only if the nature and space/time variability in water availability are compatible with the ecological requirements of a target species. We illustrate this argument with case studies drawn from California oak woodland ecosystems. We posit that identification of hydrologic refugia could form a cornerstone of climate‐cognizant conservation strategies, but that this would require improved understanding of climate change effects on key hydrologic processes, including frequently cryptic processes such as groundwater flow.

Infection risk decreases with increasing mismatch in host and pathogen environmental tolerances - A. Justin Nowakowski; Steven M. Whitfield; Evan A. Eskew; Michelle E. Thompson; Jonathan P. Rose; Benjamin L. Caraballo; Jacob L. Kerby; Maureen A. Donnelly; Brian D. Todd (Ecology Letters, 2016)
The fungal pathogen Batrachochytrium dendrobatidis ( Bd ) has caused the greatest known wildlife pandemic, infecting over 500 amphibian species. It remains unclear why some host species decline from disease‐related mortality whereas others persist. We introduce a conceptual model that predicts that infection risk in ectotherms will decrease as the difference between host and pathogen environmental tolerances (i.e. tolerance mismatch) increases. We test this prediction using both local‐scale data from Costa Rica and global analyses of over 11 000 Bd infection assays. We find that infection prevalence decreases with increasing thermal tolerance mismatch and with increasing host tolerance of habitat modification. The relationship between environmental tolerance mismatches and Bd infection prevalence is generalisable across multiple amphibian families and spatial scales, and the magnitude of the tolerance mismatch effect depends on environmental context. These findings may help explain patterns of amphibian declines driven by a global wildlife pandemic.

Detecting grizzly bear use of ungulate carcasses using global positioning system telemetry and activity data - Michael R. Ebinger; Mark A. Haroldson; Frank T. van Manen; Cecily M. Costello; Daniel D. Bjornlie; Daniel J. Thompson; Kerry A. Gunther; Jennifer K. Fortin; Justin E. Teisberg; Shannon R. Pils; P. J. White; Steven L. Cain; et al. (Oecologia, 2016)

Highly heritable resistance to root-lesion nematode (Pratylenchus thornei) in Australian chickpea germplasm observed using an optimised glasshouse method and multi-environment trial analysis - M. S. Rodda; K. B. Hobson; C. R. Forknall; R. P. Daniel; J. P. Fanning; D. D. Pounsett; S. Simpfendorfer; K. J. Moore; K. J. Owen; J. G. Sheedy; J. P. Thompson; G. J. Hollaway; et al. (Australasian Plant Pathology, 2016)

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

Bay breeze influence on surface ozone at Edgewood, MD during July 2011 - Ryan M. Stauffer; Anne M. Thompson; Douglas K. Martins; Richard D. Clark; Daniel L. Goldberg; Christopher P. Loughner; Ruben Delgado; Russell R. Dickerson; Jeffrey W. Stehr; Maria A. Tzortziou (Journal of Atmospheric Chemistry, 2015)

Differential proteomic responses of selectively bred and wild‐type Sydney rock oyster populations exposed to elevated CO 2 - E. L. Thompson; W. O'Connor; L. Parker; P. Ross; D. A Raftos (Molecular Ecology, 2015)
Previous work suggests that larvae from Sydney rock oysters that have been selectively bred for fast growth and disease resistance are more resilient to the impacts of ocean acidification than nonselected, wild‐type oysters. In this study, we used proteomics to investigate the molecular differences between oyster populations in adult Sydney rock oysters and to identify whether these form the basis for observations seen in larvae. Adult oysters from a selective breeding line (B2) and nonselected wild types ( WT ) were exposed for 4 weeks to elevated p CO 2 (856 μatm) before their proteomes were compared to those of oysters held under ambient conditions (375 μatm p CO 2 ). Exposure to elevated p CO 2 resulted in substantial changes in the proteomes of oysters from both the selectively bred and wild‐type populations. When biological functions were assigned, these differential proteins fell into five broad, potentially interrelated categories of subcellular functions, in both oyster populations. These functional categories were energy production, cellular stress responses, the cytoskeleton, protein synthesis and cell signalling. In the wild‐type population, proteins were predominantly upregulated. However, unexpectedly, these cellular systems were downregulated in the selectively bred oyster population, indicating cellular dysfunction. We argue that this reflects a trade‐off, whereby an adaptive capacity for enhanced mitochondrial energy production in the selectively bred population may help to protect larvae from the effects of elevated CO 2 , whilst being deleterious to adult oysters.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Loss of a large grazer impacts savanna grassland plant communities similarly in North America and South Africa - Stephanie Eby; Deron E. Burkepile; Richard W. S. Fynn; Catherine E. Burns; Navashni Govender; Nicole Hagenah; Sally E. Koerner; Katherine J. Matchett; Dave I. Thompson; Kevin R. Wilcox; Scott L. Collins; Kevin P. Kirkman; et al. (Oecologia, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Plant community response to loss of large herbivores differs between North American and South African savanna grasslands - Sally E. Koerner; Deron E. Burkepile; Richard W. S. Fynn; Catherine E. Burns; Stephanie Eby; Navashni Govender; Nicole Hagenah; Katherine J. Matchett; Dave I. Thompson; Kevin R. Wilcox; Scott L. Collins; Kevin P. Kirkman; et al. (Ecology, 2014)
Herbivory and fire shape plant community structure in grass‐dominated ecosystems, but these disturbance regimes are being altered around the world. To assess the consequences of such alterations, we excluded large herbivores for seven years from mesic savanna grasslands sites burned at different frequencies in North America (Konza Prairie Biological Station, Kansas, USA) and South Africa (Kruger National Park). We hypothesized that the removal of a single grass‐feeding herbivore from Konza would decrease plant community richness and shift community composition due to increased dominance by grasses. Similarly, we expected grass dominance to increase at Kruger when removing large herbivores, but because large herbivores are more diverse, targeting both grasses and forbs, at this study site, the changes due to herbivore removal would be muted. After seven years of large‐herbivore exclusion, richness strongly decreased and community composition changed at Konza, whereas little change was evident at Kruger. We found that this divergence in response was largely due to differences in the traits and numbers of dominant grasses between the study sites rather than the predicted differences in herbivore assemblages. Thus, the diversity of large herbivores lost may be less important in determining plant community dynamics than the functional traits of the grasses that dominate mesic, disturbance‐maintained savanna grasslands.

Riding the storm: the response of Plantago lanceolata to simulated tidal flooding - Mick E. Hanley; P. Y. S. Yip; S. Hoggart; D. T. Bilton; S. D. Rundle; R. C. Thompson (Journal of Coastal Conservation, 2013)

“Panta Rhei—Everything Flows”: Change in hydrology and society—The IAHS Scientific Decade 2013–2022 - A. Montanari; G. Young; H.H.G. Savenije; D. Hughes; T. Wagener; L.L. Ren; D. Koutsoyiannis; C. Cudennec; E. Toth; S. Grimaldi; G. Blöschl; M. Sivapalan; et al. (Hydrological Sciences Journal, 2013)

A polygon-based modeling approach to assess exposure of resources and assets to wildfire - Matthew P. Thompson; Joe Scott; Jeffrey D. Kaiden; Julie W. Gilbertson-Day (Natural Hazards, 2013)

Effect of prolonged exercise and pre-exercise dietary manipulation on hepatic triglycerides in trained men - N. A. Johnson; D. van Overbeek; P. G. Chapman; M. W. Thompson; T. Sachinwalla; J. George (European Journal of Applied Physiology, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Studies on the effect of temperature and pH on the inactivation of fish viral and bacterial pathogens - P F Dixon; D A Smail; M Algoët; T S Hastings; A Bayley; H Byrne; M Dodge; A Garden; C Joiner; E Roberts; D Verner‐Jeffreys; F Thompson (Journal of Fish Diseases, 2012)
Disposal of fish by‐products in the European Community must comply with Regulation (EC) No 1069/2009 which categorizes animal by‐products according to risk, and specifies methods of disposal of by‐products according to that risk. There is provision under the regulation for composting or ensiling to be used for by‐products from aquatic animals. Biosecurity considerations require knowledge of the parameters of time and temperature, or time and pH, required to inactivate any fish pathogens that may be present. To provide those data, we undertook laboratory studies on the inactivation of a number of fish pathogenic viruses and bacteria at 60 °C, pH 4.0 and pH 12.0 as a preliminary to conducting subsequent trials with the most resistant viruses and bacteria in fish tissues. The most resistant bacterium to 60 °C, pH 4.0 as well as pH 12.0 was Lactococcus garvieae . Its concentration was reduced to the level of sensitivity of the test after 24–48 h exposure to 60 °C, but it survived for at least 7 days at pH 4.0 and 14 days at pH 12.0. The most resistant virus to 60 °C was infectious pancreatic necrosis virus, and to pH 12.0 was infectious salmon anaemia virus. The majority of the viruses tested survived exposure to pH 4.0 for up to 28 days. The results suggest that the process of acid ensiling alone is not an effective method for the inactivation of many viral and bacterial pathogens, and fish by‐products would need further treatment by a method approved under the regulation following ensiling, whereas alkaline or heat treatment are likely to provide an increased degree of biosecurity for on‐farm processing of mortalities.

Evolution of anthropogenic and biomass burning emissions of air pollutants at global and regional scales during the 1980–2010 period - Claire Granier; Bertrand Bessagnet; Tami Bond; Ariela D’Angiola; Hugo Denier van der Gon; Gregory J. Frost; Angelika Heil; Johannes W. Kaiser; Stefan Kinne; Zbigniew Klimont; Silvia Kloster; Jean-François Lamarque; et al. (Climatic Change, 2011)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

A Real-Time Risk Assessment Tool Supporting Wildland Fire Decisionmaking - David E. Calkin; Matthew P. Thompson; Mark A. Finney; Kevin D. Hyde (Journal of Forestry, 2011)
Development of appropriate management strategies for escaped wildland fires is complex. Fire managers need the ability to identify, in real time, the likelihood that wildfire will affect valuable developed and natural resources (e.g., private structures, public infrastructure, and natural and cultural resources). These determinations help guide where and when aggressive suppression is required to protect values and when fire may be allowed to burn to enhance ecosystem conditions. This article describes the primary components of the Wildland Fire Decision Support System (WFDSS), a geospatial decision support system developed by the US Forest Service. WFDSS provides state-of-the-art wildfire risk analysis, decision documentation, and long-term implementation planning. In particular, we describe how the two primary decision support analysis components of WFDSS, Fire Spread Probability (fire behavior) and Rapid Assessment of Values at Risk (resource assessment), fit into the current state of risk assessment tools for wildfire suppression decisionmaking.

Mutation deep within an intron of MSH2 causes Lynch syndrome - Mark Clendenning; Daniel D. Buchanan; Michael D. Walsh; Belinda Nagler; Christophe Rosty; Bryony Thompson; Amanda B. Spurdle; John L. Hopper; Mark A. Jenkins; Joanne P. Young (Familial Cancer, 2011)

Assessment of flipper tag site healing in gray seal pups using thermography - W. Paterson; P. P. Pomeroy; C. E. Sparling; S. Moss; D. Thompson; J. I. Currie; D. J. McCafferty (Marine Mammal Science, 2011)
Infrared thermography was used to monitor the healing process at flipper tag sites in gray seal ( Halichoerus grypus ) pups. We tested the hypothesis that tagging would result in a rise in surface temperature associated with tag site healing processes compared with adjacent untagged areas of the flipper. Prior to tagging thermal images were recorded of the dorsal side of hind flippers of pups tagged in early lactation ( n = 20) and at weaning ( n = 19) on the Isle of May, Scotland (56°11′N, 02°33′W) from October to December 2008. Pups tagged in early lactation were sampled again at late lactation, at weaning and then every 3 d for an average of 29 d post‐tagging while pups tagged at weaning were sampled every 3 d for an average of 17 d post‐tagging. Tag sites were also scored for signs of infection or swelling at each sampling. Results showed that (1) small temperature increases associated with wound healing processes around the tag site returned to pre‐tagging levels before animals leave the island and (2) there was little evidence of tagging‐related infections or tag loss irrespective of age at tagging.

AKT1 polymorphisms are associated with risk for metabolic syndrome - Joseph M. Devaney; Heather Gordish-Dressman; Brennan T. Harmon; Margaret K. Bradbury; Stephanie A. Devaney; Tamara B. Harris; Paul D. Thompson; Priscilla M. Clarkson; Thomas B. Price; Theodore J. Angelopoulos; Paul M. Gordon; Niall M. Moyna; et al. (Human Genetics, 2011)

Detection of Polymyxa graminis in a barley crop in Australia - J. P. Thompson; T. G. Clewett; R. E. Jennings; J. G. Sheedy; K. J. Owen; D. M. Persley (Australasian Plant Pathology, 2011)

Association of red‐mark syndrome with a Rickettsia ‐like organism and its connection with strawberry disease in the USA - M Metselaar; K D Thompson; R M L Gratacap; M J L Kik; S E LaPatra; S J Lloyd; D R Call; P D Smith; A Adams (Journal of Fish Diseases, 2010)
Red‐mark syndrome (RMS), a disease seen mostly in rainbow trout, Oncorhynchus mykiss , is of unknown aetiology. The research presented here indicates the presence of an intracellular bacterium in RMS‐affected fish. A positive reaction was observed using immunohistochemistry (IHC) with skin lesions, liver, kidney and spleen of affected fish sampled from several locations within the United Kingdom using two different polyclonal antisera raised against Piscirickettsia salmonis . The same reaction was also seen with a number of different anti‐ P. salmonis monoclonal antibodies (MAbs). A disease with similar clinical signs to RMS, referred to as strawberry disease (SD), has been reported in the USA. A Rickettsia ‐like organism (RLO) has recently been associated with SD based on analysis of 16S rDNA sequences. Using the same panel of anti‐ P. salmonis antibodies used to screen the RMS samples, similar staining was obtained in tissue of SD‐affected fish by IHC. A polymerase chain reaction (PCR) using RLO‐specific primers was also performed on RMS‐affected fish from the United Kingdom, and the samples were positive for the RLO 16S rRNA sequence. These findings suggest that the same aetiological agent may be responsible for RMS in the United Kingdom and SD in the USA.

A polymorphism near IGF1 is associated with body composition and muscle function in women from the Health, Aging, and Body Composition Study - Matthew C. Kostek; Joseph M. Devaney; Heather Gordish-Dressman; Tamara B. Harris; Paul D. Thompson; Priscilla M. Clarkson; Theodore J. Angelopoulos; Paul M. Gordon; Niall M. Moyna; Linda S. Pescatello; Paul S. Visich; Robert F. Zoeller; et al. (European Journal of Applied Physiology, 2010)

Erratum to: Integrating advanced technologies for optimization of aerial herbicide applications - D. Thompson; D. Chartrand; B. Staznik; J. Leach; P. Hodgins (New Forests, 2010)

Integrating advanced technologies for optimization of aerial herbicide applications - D. Thompson; D. Chartrand; B. Staznik; J. Leach; P. Hodgins (New Forests, 2010)

Guidelines for the treatment of marine mammals in field research - N. J. Gales; W. D. Bowen; D. W. Johnston; K. M. Kovacs; C. L. Littnan; W. F. Perrin; J. E. Reynolds; P. M. Thompson (Marine Mammal Science, 2009)

Allometric scaling of isometric biceps strength in adult females and the effect of body mass index - Robert F. Zoeller; Eric D. Ryan; Heather Gordish-Dressman; Thomas B. Price; Richard L. Seip; Theodore J. Angelopoulos; Niall M. Moyna; Paul M. Gordon; Paul D. Thompson; Eric P. Hoffman (European Journal of Applied Physiology, 2008)

Antioxidant Properties of Cultivars and Selections from the Colorado Potato Breeding Program - C. Stushnoff; D. Holm; M. D. Thompson; W. Jiang; H. J. Thompson; N. I. Joyce; P. Wilson (American Journal of Potato Research, 2008)

Impairment of movement-associated brain deactivation in multiple sclerosis: further evidence for a functional pathology of interhemispheric neuronal inhibition - S. C. Manson; C. Wegner; M. Filippi; F. Barkhof; C. Beckmann; O. Ciccarelli; N. De Stefano; Christian Enzinger; F. Fazekas; F. Agosta; A. Gass; J. Hirsch; et al. (Experimental Brain Research, 2008)

Toxicity of the Systemic Insecticide, Imidacloprid, to Forest Stream Insects and Microbial Communities - D. P. Kreutzweiser; K. P. Good; D. T. Chartrand; T. A. Scarr; D. G. Thompson (Bulletin of Environmental Contamination and Toxicology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Does cigarette smoking increase plasma urotensin II concentrations? - S. J. Gold; J. P. Thompson; J. P. Williams; E. E. F. Helm; J. Sadler; W. Song; L. L. Ng; D. G. Lambert (European Journal of Clinical Pharmacology, 2007)

Modelling the impacts of removing seal predation from Atlantic salmon, Salmo salar , rivers in Scotland: a tool for targeting conflict resolution - J. R. A. BUTLER; S. J. MIDDLEMAS; I. M. GRAHAM; P. M. THOMPSON; J. D. ARMSTRONG (Fisheries Management and Ecology, 2006)
Bioenergetics were used to model the potential impacts on adult Atlantic salmon, Salmo salar L., stocks and rod fisheries of removing harbour seals, Phoca vitulina L., from three rivers of different scales in the Moray Firth, Scotland, viz: the Spey (large), Conon (medium) and Moriston (small). Overall, seals had the greatest impact on the Moriston, where removal of a single animal could increase cumulative catch by 17% during the fishing season. On the Conon and Spey the impacts were negligible, and resulted in increased catches of 33% in rivers with monthly rod catches ≤10 fish, but declined to 34 fish. The outputs of the models are qualitative, but provide a management tool for targeting action to resolve seal‐salmon fishery conflict. Smaller salmon population units, and spring salmon sub‐stocks and fisheries in particular, are most vulnerable to predation. The merit of this approach is discussed regarding the management of Special Areas of Conservation for salmon and seals.

Plasma Hsp72 is higher in runners with more serious symptoms of exertional heat illness - P. A. Ruell; M. W. Thompson; K. M. Hoffman; J. R. Brotherhood; D. A. B. Richards (European Journal of Applied Physiology, 2006)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Identifying brain regions for integrative sensorimotor processing with ankle movements - O. Ciccarelli; A. T. Toosy; J. F. Marsden; C. M. Wheeler-Kingshott; C. Sahyoun; P. M. Matthews; D. H. Miller; A. J. Thompson (Experimental Brain Research, 2005)

Land Disposal of Centrate from Biosolids Production - D. J. Baumgartner; E. P. Glenn; T. L. Thompson; B. A. Skeen (Water, Air, & Soil Pollution, 2005)

Oligogenic combinations associated with breast cancer risk in women under 53years of age - Christopher E. Aston; David A. Ralph; Dominique P. Lalo; Sharmila Manjeshwar; Bobby A. Gramling; Daniele C. DeFreese; Amy D. West; Dannielle E. Branam; Linda F. Thompson; Melissa A. Craft; Debra S. Mitchell; Craig D. Shimasaki; et al. (Human Genetics, 2005)

MULTISITE MARK-RECAPTURE FOR CETACEANS: POPULATION ESTIMATES WITH BAYESIAN MODEL AVERAGING - J. W. Durban; D. A. Elston; D. K. Ellifrit; E. Dickson; P. S. Hammond; P. M. Thompson (Marine Mammal Science, 2005)

Molecular and ecological evidence for small‐scale isolation by distance in an endangered damselfly, Coenagrion mercuriale - P. C. WATTS; J. R. ROUQUETTE; I. J. SACCHERI; S. J. KEMP; D. J. THOMPSON (Molecular Ecology, 2004)
Coenagrion mercuriale (Charpentier) (Odonata: Zygoptera) is one of Europe's most threatened damselflies and is listed in the European Habitats directive. We combined an intensive mark‐release‐recapture (MRR) study with a microsatellite‐based genetic analysis for C. mercuriale from the Itchen Valley, UK, as part of an effort to understand the dispersal characteristics of this protected species. MRR data indicate that adult damselflies are highly sedentary, with only a low frequency of interpatch movement that is predominantly to neighbouring sites. This restricted dispersal leads to significant genetic differentiation throughout most of the Itchen Valley, except between areas of continuous habitat, and isolation by distance (IBD), even though the core populations are separated by less than 10 km. An urban area separating some sites had a strong effect on the spatial genetic structure. Average pairwise relatedness between individual damselflies is positive at short distances, reflecting fine‐scale genetic clustering and IBD both within‐ and between‐habitat patches. Damselflies from a fragmented habitat have higher average kinship than those from a large continuous population, probably because of poorer dispersal and localized breeding in the former. Although indirect estimates of gene flow must be interpreted with caution, it is encouraging that our results indicate that the spatial pattern of genetic variation matches closely with that expected from direct observations of movement. These data are further discussed with respect to possible barriers to dispersal within the study site and the ecology and conservation of C. mercuriale . To our knowledge, this is the first report of fine‐scale genetic structuring in any zygopteran species.

Effects of model resolution and subgrid-scale physics on the simulation of precipitation in the continental United States - J. P. Iorio; P. B. Duffy; B. Govindasamy; S. L. Thompson; M. Khairoutdinov; D. Randall (Climate Dynamics, 2004)

Soil Sampling Techniques for Alabama, USA Grain Fields - A. N. Thompson; J. N. Shaw; P. L. Mask; J. T. Touchton; D. Rickman (Precision Agriculture, 2004)

Physical disturbance of an upland grassland influences the impact of elevated UV‐B radiation on metabolic profiles of below‐ground micro‐organisms - L. M. Avery; P. C. Thorpe; K. Thompson; N. D. Paul; J. P. Grime; H. M. West (Global Change Biology, 2004)
This investigation determined the response of soil microbial communities to enhanced UV‐B radiation and disturbance in upland grassland. A factorial field experiment encompassing two levels of UV‐B supplementation (simulating ambient and a 30% increase in stratospheric ozone) and two levels of disturbance (disturbed and undisturbed) was established at Buxton Climate Change Impacts Laboratory, Derbyshire, UK, and maintained for 7 years prior to sampling. Enhanced UV‐B increased microbial utilization of carbohydrates, carboxylic acids, polymers and aromatic compounds present in Biolog® GN plates when inoculated with soils taken from disturbed plots, but did not affect carbon utilization of soil microbial communities associated with undisturbed plots (UV‐B×Disturbance interaction, P UV‐B treatment did not affect numbers of bacteria or fungi. Direct microscopic counts showed fewer bacteria in soil originating from disturbed plots than from undisturbed plots (Disturbance, P P UV‐B treatment did not affect total plant biomass within undisturbed plots or the biomass of individual groupings of grasses, forbs and mosses. Per cent root length colonized by arbuscular mycorrhizal fungi (AMF) was not affected by enhanced UV‐B radiation in the undisturbed plots. Neither AMF nor plant biomass was measured in disturbed plots. The key findings of this study show that UV‐B‐mediated alterations in carbon utilization occurred in soil microbial communities subjected to disturbance, but such changes were not observed in communities sampled from undisturbed grassland. Differences in the catabolic potential of microbial communities from disturbed grassland subjected to enhanced UV‐B are probably related to plant‐mediated changes in resource availability or quality.

Functional mechanisms underlying cetacean distribution patterns: hotspots for bottlenose dolphins are linked to foraging - G. D. Hastie; B. Wilson; L. J. Wilson; K. M. Parsons; P. M. Thompson (Marine Biology, 2004)

Mid-Holocene climates of the Americas: a dynamical response to changed seasonality - S. P. Harrison; J. E. Kutzbach; Z. Liu; P. J. Bartlein; B. Otto-Bliesner; D. Muhs; I. C. Prentice; R. S. Thompson (Climate Dynamics, 2003)

Characterisation of the expression of a novel constitutive maize promoter in transgenic wheat and maize - S. Rasco-Gaunt; D. Liu; C. Li; A. Doherty; K. Hagemann; A. Riley; T. Thompson; C. Brunkan; M. Mitchell; K. Lowe; E. Krebbers; P. Lazzeri; et al. (Plant Cell Reports, 2003)

Fate and Persistence of Azadirachtin A Following Applications to Mesocosms in a Small Forest Lake - D. G. Thompson; D. P. Kreutzweiser; B. Staznik; D. Chartrand; S. Capell (Bulletin of Environmental Contamination and Toxicology, 2002)

Ankerite carbonatite from Swartbooisdrif, Namibia: the first evidence for magmatic ferrocarbonatite - R. Thompson; P. Smith; S. Gibson; D. Mattey; A. Dickin (Contributions to Mineralogy and Petrology, 2002)

Interdisciplinary Irrigated Precision Farming Research - D. F. Heermann; J. Hoeting; S. E. Thompson; H. R. Duke; D. G. Westfall; G. W. Buchleiter; P. Westra; F. B. Peairs; K. Fleming (Precision Agriculture, 2002)

Risedronate Pharmacokinetics and Intra- and Inter-Subject Variability Upon Single-Dose Intravenous and Oral Administration - David Y. Mitchell; William H. Barr; Rachelle A. Eusebio; Karen A. Pallone Stevens; Frank P. Duke; Darrell A. Russell; John D. Nesbitt; James H. Powell; Gary A. Thompson (Pharmaceutical Research, 2001)

High pressure fluids in the system MgO–SiO2–H2O under upper mantle conditions - R. Stalder; P. Ulmer; A. Thompson; D. Günther (Contributions to Mineralogy and Petrology, 2001)

A Piscirickettsia salmonis ‐like organism in grouper, Epinephelus melanostigma , in Taiwan - S‐C Chen; P‐C Wang; M‐C Tung; K D Thompson; A Adams (Journal of Fish Diseases, 2000)

Effects of the nicotinic antagonist mecamylamine on inspection time - J. C. Thompson; C. Stough; D. Ames; C. Ritchie; P. J. Nathan (Psychopharmacology, 2000)

Plant Uptake Response to Metals and Nitrate in Simulated Uranium Mill Tailings Contaminated Groundwater - D. J. Baumgartner; E. P. Glenn; R. O. Kuehl; T. L. Thompson; J. F. Artiola; S. E. Menke; R. A. Saar; G. S. Moss; M. A. Algharaibeh (Water, Air, & Soil Pollution, 2000)

Laboratory Kinetic Studies of the Reactions of Cl Atoms with Species of Biogenic Origin: δ3-Carene, Isoprene, Methacrolein and Methyl Vinyl Ketone - Carlos E. Canosa-Mas; Hilary R. Hutton-Squire; Martin D. King; David J. Stewart; Katherine C. Thompson; Richard P. Wayne (Journal of Atmospheric Chemistry, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Multiple origins of polyploidy and the geographic structure of Heuchera grossulariifolia - K. A. SEGRAVES; J. N. THOMPSON; P. S. SOLTIS; D. E. SOLTIS (Molecular Ecology, 1999)
Multiple origins of polyploidy from an ancestral diploid plant species were investigated using restriction site polymorphism and sequence variation in the chloroplast DNA (cpDNA) of Heuchera grossulariifolia (Saxifragaceae). Phylogenetic analysis indicated that autopolyploidy has arisen at least twice in the evolutionary history of this species and potentially up to as many as seven times. These results suggest a greater range of independent polyploid origins as compared to a previous study of H. grossulariifolia using cpDNA restriction sites that indicated a minimum of three independent origins. Moreover, most polyploid populations did not contain cpDNA haplotypes from a single origin, but rather combined haplotypes from at least two polyploid origins. Past migration among polyploid populations of independent origin or localized polyploid formation may explain the distribution of polyploid haplotypes within and among populations. The analysis also revealed a discrepancy between relatedness and geographical location. In nearly all sympatric populations of diploids and polyploids, polyploids had the same cpDNA haplotypes as diploids from a geographically remote population. This geographical discordance has several possible explanations, including small sample sizes, extinction of parental diploid haplotypes, chloroplast introgression, and homoplasy in the cpDNA sequence data. We conclude that the recurrent formation of polyploids is an important evolutionary mechanism in the diversification of H. grossulariifolia .

Activation of nuclear factor kappa B in Crohn's disease - R. D. Ellis; J. R. Goodlad; G. A. Limb; J. J. Powell; R. P. H. Thompson; N. A. Punchard (Inflammation Research, 1998)

Probing termite social systems through allozyme and mtDNA analysis: a case study of Nasutitermes nigriceps and Nasutitermes costalis (Isoptera, Termitidae) - G. J. Thompson; P. D. N. Hebert (Insectes Sociaux, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Molecular scatology: the use of molecular genetic analysis to assign species, sex and individual identity to seal faeces - J. Z. Reed; D. J. Tollit; P. M. Thompson; W. Amos (Molecular Ecology, 1997)
Seals and commercial fisheries are potential competitors for fish and cephalopods. Research into the diet of British seal species has been based on conventional dietary analyses, but these methods often do not allow assignment of species identity to scat samples. We present a protocol for obtaining DNA from seal scat (faecal) samples which can be used in polymerase chain reactions to amplify both nuclear and mitochondrial DNA. This can provide a method of identifying the species, sex and individual identity of the seal, from a particular scat sample. Combined with conventional dietary analyses these techniques will allow us to assess sources of variation in seal diet composition. Scat samples have been collected from intertidal haul‐out sites around the inner Moray Firth, north‐east Scotland. We have assessed methods to extract and purify faecal DNA, a combination of DNA from the individual seal, prey items, and gut bacteria, for use in PCR. Controls using faecal and blood samples from the same individual have enabled microsatellite primer sets from four pinniped species to be tested. Approximately 200 scat samples have been examined for species identity and individual matches. This study will provide essential information for the assessment of interactions between seals and commercial or recreational fisheries.

Methylosulfonomonas methylovora gen. nov., sp. nov., and Marinosulfonomonas methylotropha gen. nov., sp. nov.: novel methylotrophs able to grow on methanesulfonic acid - Andrew J. Holmes; D. P. Kelly; Simon C. Baker; A. S. Thompson; Paolo De Marco; Elizabeth M. Kenna; J. Colin Murrell (Archives of Microbiology, 1997)

Organochlorine pesticide contamination in neotropical migrant passerines - R. G. Harper; J. A. Frick; A. P. Capparella; B. Borup; M. Nowak; D. Biesinger; C. F. Thompson (Archives of Environmental Contamination and Toxicology, 1996)

Genetic interrelationships of proteolyticClostridium botulinum types A, B, and F and other members of theClostridium botulinum complex as revealed by small-subunit rRNA gene sequences - R. A. Hutson; D. E. Thompson; P. A. Lawson; R. P. Schocken-Itturino; E. C. Bttger; M. D. Collins (Antonie van Leeuwenhoek, 1994)

DNA restriction-fragment variation in the gene family encoding high molecular weight (HMW) glutenin subunits of wheat - N. P. Harberd; D. Bartels; R. D. Thompson (Biochemical Genetics, 1986)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

s of papers presented at Annual Meeting - F. Heiligman; J. R. Wagner; WM. G. Hoyman; Jack R. Wallin; D. R. Isleib; N. R. Thompson; Robert H. Johansen; Knutson Kenneth; Carl J. Eide; F. A. Krantz; Florian Lauer; F. I. Lauer; et al. (American Journal of Potato Research, 1957)